Comparison between school and home-based dental health promotion in improving knowledge, parental attitude and dental health of children with mild disabilities - Putri Raisah; Rosa Amalia; Bambang Priyono (Dental Journal (Majalah Kedokteran Gigi), 2021)
Background: In general, children with physical disabilities have a lower level of oral hygiene compared to able-bodied children because their access to dental health care services is affected by their physical limitations. The level of oral hygiene available to children with disabilities can be improved with the involvement of parents/caregivers equipped with good knowledge and attitudes regarding oral health. Purpose: Determine the difference between the effectiveness of school and home visit-based dental health promotion in improving the knowledge and attitudes of parents/caregivers and students regarding oral hygiene as well as lowering the dental plaque scores of students with mild physical disabilities. Methods: This study is quasi-experimental and uses the two-group pretest–posttest design. The study’s design was created with a model of one observation before intervention (O1), two interventions (X1-2) and two observations after intervention (O2-3). The study samples are students with mild physical disabilities aged 8–15 years old in special needs school, or sekolah luar biasa (SLB), in Sleman, Yogyakarta, and their parents/caregivers. The locations of the study were SLBs and the respondents’ homes. The study instrument was a knowledge test for students with mild physical disabilities and their parents/caregivers, along with a questionnaire on the parents/caregivers’ attitudes towards oral and dental health. Plaque control examinations for students with mild physical disabilities were conducted using the O’Leary index. Results: School-based oral health promotion was better at improving the attitudes of parents/caregivers to oral hygiene than the home visits (p<0.05). Both school-based and home visit-based oral health promotion was effective in furthering the oral hygiene knowledge of students with mild disabilities and their parents/caregivers as well as in improving the students’ dental plaque scores (p>0.05). Conclusion: The school based-oral health promotion model was more effective in improving attitudes of the students’ parents/caregivers. Both the school-based and the home visit-based oral health promotion models were equally effective in enhancing the knowledge of parents/caregivers, along with the knowledge and dental plaque scores of students with mild disabilities.